Changes in weight and body fat after use of tetracycline and Lactobacillus gasseri in rats - Jorge José Marciano; Fernando de Sá Del Fiol; Alessandra Cristina Marciano Tardelli Ferreira; Maria Cláudia Marques; Luciane Lopes Santana (Universidade de São Paulo, 2017)
ABSTRACT Recent studies have shown a role of intestinal microbiota in obesity. The consumption of antibiotics in the last 70 years has led to changes in intestinal microbiota, which has led to weight gain and body fat accumulation. To evaluate the possibility of weight gain induced by antibiotics and the possible protective effect of probiotics, we divided 45 animals (Rattus norvegicus) into groups and administered the following treatments over two weeks: tetracycline, tetracycline + Lactobacillus gasseri, and NaCl. The animals were weighed over the course of 8 weeks, and at the end of the treatment period, they were measured and subjected to bioelectrical impedance analysis. The results show that the group receiving tetracycline alone had a higher body mass index (p=0.030), a greater Lee index (p=0.008), and a lower body water percentage than the control group, indicating a greater accumulation of body fat. The group receiving the probiotics with tetracycline presented similar results to the control group, indicating a possible protective effect of body fat accumulation in the group receiving tetracycline alone. The results show that tetracycline increased the concentration of body fat, and the use of probiotics was associated with an ability to protect the animals from the pro-obesity effect.